Relatos autobiográficos de uma professora atuante em uma escola rural: sentidos e significados à leitura - Santi, Lucila Gavioli (2013)
This work shows the results of a research in education linked to the research line Formação, Saberes e Desenvolvimento Profissional (LP1), of Programa de Pós-Graduação em Educação of the Universidade Federal de Santa Maria. By the autobiographic method I tried to study the history of life of a rural teacher from Santa Maria, RS. I searched to show her reader s experiences and her role as a reading mediator and also how significant the acts of reading and writing are. Therefore, I established lines on rural education and on the formation of rural readers, detailing the reading experiences of the teacher with a multigraded group in the year 2012. To base the writing of this thesis, I used some authors points of view about qualitative research: Bodgar-Biklen(1994) and Minayo(1993). Referring to theoretical approach about the history of life, the studies of Nóvoa (1992), Abrahão (2006) and Oliveira (2006) were used. For the reflections about rural education, I theorized with Arroyo, Caldart, Molina and others. On readers formation, I made a theoretical deepening with studies of Barcelos, Silva and Paiva among others. The study is divided in six chapters, three of which are based in the following analysis categories: first readings, school times, formation, practicing and mediating reading in the classroom. With this research I wish somehow inspire teachers that dedicate their work to the reading practice.